Analisis Hambatan Penerapan Perpres Nomor 14 Tahun 2021 Tentang Pengadaan dan Pelaksanaan Vaksinasi dalam Rangka Penangulangan Pandemi Corona di Aceh - Nazaruddin, Nazaruddin; Nazaruddin, M; Fazil, Muhammad (Jurnal Transparansi Publik (JTP), 2024)
This research examines policies for handling the COVID-19 pandemic in Indonesia based on Presidential Decree Number 14 of 2021 concerning procurement and implementation of vaccinations. This policy has been implemented in every province in Indonesia, but has not run as smoothly as it should, as happened in North Aceh District. According to the results of the author's search, the progress of vaccination is still low and has not reached the specified target of 70% by December 31, 2021. Researchers use qualitative research methods that are descriptive in the form of written or spoken words; what is observed are people and their behavior; the researcher is the key instrument; the data source is natural background; the data analysis is carried out inductively; and the results emphasize meaning rather than generalization. The results of the study show that the implementation of vaccinations in North Aceh District during 2021 has not reached the target due to information problems among the people of North Aceh District. The form of the problem is the distrust of the people of North Aceh towards the contents of the vaccine. So that there is still poor communication between the Implementer or the North Aceh District COVID-19 Task Force team and the people of North Aceh District, socialization should not be carried out so slowly; events circulating more quickly in this community are a sign of negligence. The structure should be well-planned, and it should form the socialization team through the media so that the true news about this vaccine is read by the public first rather than the hoax news that propagates this vaccine.